Efforts to Improve Community Policing on Patrols Dialogue of Samapta Unit to Prevent Theft in Framework for Realizing Public Order and Security at The Kediri Police - Syahlana, Salva Wajdi; Icasia Althaf, Kevin; Torro Ignatius Paskah Boseke, Timothy (Tanggon Kosala, 2025)
The crime of theft with aggravation (Curat) is a type of crime that ranks first of all categories of crimes that occur in Indonesia. Based on data from the Kediri Police investigation unit, the number of Curat crimes from 2020 to July 2023 has reached 313 cases. This Kamtibmas disturbance situation also occurred in the city of Kediri. Repressive law enforcement has an essential role in the eradication of criminal acts, however, preemptive and preventive measures as prevention are far more critical so that people Do not become victims or even perpetrators of cheating crimes. However, the rampant crime in the jurisdiction of the Kediri Regional Police proves that preventive measures carried out through Dialogical Patrols by prioritizing the Polmas have not brought optimal results. In this writing, the author applies a qualitative descriptive method with the consideration that the problems raised by the author are more than a study of a case. In this study, the author uses a type of case study research, namely understanding, studying, and researching the obstacles faced in the implementation of Community Policing Dialogical Patrols in the Samapta Unit to prevent curat crime and maintain the situation of Kamtibmas in the jurisdiction of the Kediri Regional Police. The author of this study will examine a variable with other variables to produce an explanatory statement. The obstacles faced by the Samapta Unit are related to the limited number of members who must reach a broad jurisdiction. The materials and techniques applied in message delivery have not been updated. Data on potential crime risk in various areas has not been updated, so members obtain little information. Efforts to increase Community Policing in the Dialogical Patrols of the Samapta Unit to prevent fraudulent crimes to realize the maintenance of Kamtibmas in the jurisdiction of the Kediri Police. The competency development of Samapta Unit members includes educational programs designed to expand skills and knowledge.